Switch to Aflibercept in the Treatment of Neovascular AMD: Long-Term Results - Pedro Neves Cardoso; Ana Fernanda Pinheiro; Jorge Meira; Ana Catarina Pedrosa; Manuel S. Falcão; João Pinheiro-Costa; Fernando Falcão-Reis; Ângela M. Carneiro (Journal of Ophthalmology)
Purpose. To report the long-term clinical outcomes after switching from intravitreal bevacizumab or ranibizumab to aflibercept therapy in eyes with AMD. Methods. Retrospective analysis of changes in BCVA, SD-OCT image, and frequency of injections after 1, 2, and 3 years of follow-up. Results. 164 eyes were analyzed, 101 eyes switched from bevacizumab (group 1) and 63 from ranibizumab (group 2). One year after the switch, there was an overall nonsignificant mean decrease of 2 ETDRS letters in BCVA. Three years after, there was an overall mean decrease of 7 ETDRS letters, which was statistically significant. A significant improvement in the mean CRT was found at 1, 2, and 3 years. There was a significant decrease in the mean number of injections per year (7.8 to 6.5, p<0.005) between the first and third year. Conclusion. Aflibercept can be useful in the management of refractory neovascular AMD, with a good morphological response. However, in the long-term, BCVA stabilization was not achieved.